Determination of the relationships between hyperemesis gravidarum and systemic inflammation markers: a case‒control study - Fikriye Işıl Adıgüzel; Serhat Altınkaya; Sadık Kükrer; Ahmet Zeki Nessar; Gülsüm Uysal; Cevdet Adıgüzel (BMC Pregnancy and Childbirth)
Abstract Background We conducted our study to investigate the relationships between hyperemesis gravidarum (HEG) and inflammatory markers such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR). Materials and methods A total of 150 pregnant women diagnosed with HEG and 150 controls were included in our study. The data analysed included demographic variables, complete blood count results, and urinary ketonuria levels. Results We found that the NLR, PLR and MLR were significantly greater in HEG patients than in controls (p < 0.05), indicating a potential role of systemic inflammation in the pathophysiology of HEG. Receiver operating characteristic (ROC) analysis revealed that these markers had moderate discriminative power, suggesting their utility as adjunctive diagnostic tools in clinical settings. However, no correlation was found between inflammatory markers and the severity of ketonuria. Conclusions The NLR, PLR and MLR can be used as indicators of HEG as a result of the inflammatory process in pregnant women with HEG.